Feasibility and safety of two different surgical routes for the eradication of recto‐vaginal endometriosis with vaginal mucosa infiltration (Endo‐Vag‐r study). (27th February 2020) - Raimondo, Diego; Turco, Luigi C.; Cosentino, Francesco; Mabrouk, Mohamed; Mastronardi, Manuela; Borghese, Giulia; Giaquinto, Ilaria; Vargiu, Virginia; Fagotti, Anna; Meriggiola, Maria C.; Chiantera, Vito; Scambia, Giovanni; et al.
Abstract: Introduction: Recto‐vaginal endometriosis surgical management needing partial colpectomy is a surgically challenging condition and has been associated with a notable risk of major postoperative complications. In the present study we sought to compare feasibility and safety of total laparoscopic (TL) and vaginal‐assisted (VA) routes in women affected by symptomatic recto‐vaginal endometriosis with vaginal mucosa infiltration scheduled for minimally invasive surgery. Material and methods: Multi‐centric, retrospective cohort study on medical records of consecutive reproductive age women submitted to complete macroscopic eradication of symptomatic recto‐vaginal endometriosis with vaginal mucosa infiltration between March 2013 and November 2017. The two groups were compared in terms of preoperative data and surgical outcomes. Results: 84 women were included in the study (TL = 57 and VA = 27). The two groups were comparable in terms of preoperative, surgical and postoperative data. The major postoperative complications rate was 5.3% (3 of 57) in the TL group and 7.4% (2 of 27) in the VA group, without a significant difference. In the TL group we reported one case of bowel anastomosis dehiscence and two cases of pelvic abscess. In the VA group, one case of small bowel perforation after extensive adhesiolysis treated with ileal resection and one case of rectal sub‐occlusion after segmental resection and mechanical anastomosis were noticed. Conclusions: In women affected by recto‐vaginal endometriosis with vaginal mucosal infiltration, perioperative outcomes do not seem to be influenced by the surgical route adopted.